2022
DOI: 10.1038/s41467-022-35143-2
|View full text |Cite
|
Sign up to set email alerts
|

HSP90-CDC37-PP5 forms a structural platform for kinase dephosphorylation

Abstract: Activation of client protein kinases by the HSP90 molecular chaperone system is affected by phosphorylation at multiple sites on HSP90, the kinase-specific co-chaperone CDC37, and the kinase client itself. Removal of regulatory phosphorylation from client kinases and their release from the HSP90-CDC37 system depends on the Ser/Thr phosphatase PP5, which associates with HSP90 via its N-terminal TPR domain. Here, we present the cryoEM structure of the oncogenic protein kinase client BRAFV600E bound to HSP90-CDC3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…The core structural principles of Cdc37 mediated client recruitment to Hsp90 appear to remain constant across its large range of client diversity. Across other client–Hsp90–Cdc37 complexes with canonical soluble kinase clients (Cdk4, RAF1, B-raf) (García-Alonso et al, 2022; Oberoi et al, 2022; Verba et al, 2016), we see a conserved role for Cdc37 in client recruitment by associating with the C-lobe at the N-, C-lobe interface (Supplemental Figure 2A). In these complexes we see high levels of structural conservation for the Hsp90–Cdc37 (Cα RMSDs of 1.4-3.3 Å for Hsp90 and 1.5-2.5 Å for Cdc37), while the client is structurally most homogenous at the interface with Cdc37, though less structurally conserved overall (Cα RMSDs of 3.5-11.6 Å).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The core structural principles of Cdc37 mediated client recruitment to Hsp90 appear to remain constant across its large range of client diversity. Across other client–Hsp90–Cdc37 complexes with canonical soluble kinase clients (Cdk4, RAF1, B-raf) (García-Alonso et al, 2022; Oberoi et al, 2022; Verba et al, 2016), we see a conserved role for Cdc37 in client recruitment by associating with the C-lobe at the N-, C-lobe interface (Supplemental Figure 2A). In these complexes we see high levels of structural conservation for the Hsp90–Cdc37 (Cα RMSDs of 1.4-3.3 Å for Hsp90 and 1.5-2.5 Å for Cdc37), while the client is structurally most homogenous at the interface with Cdc37, though less structurally conserved overall (Cα RMSDs of 3.5-11.6 Å).…”
Section: Resultsmentioning
confidence: 86%
“…The Cricetulus griseus HSP90β and Cdc37 show remarkable sequence conservation in comparison to the human equivalents, at 99.7 and 94.2% identity, respectively. This native pulldown strategy contrasts with the structures of Hsp90–Cdc37 in complex with soluble kinases (García-Alonso et al, 2022; Oberoi et al, 2022; Verba et al, 2016), for which Hsp90 and Cdc37 had to be overexpressed to obtain complex suitable for imaging. Three-dimensional reconstruction of our GC-C–Hsp90–Cdc37 particles generated a 3.9 Å resolution map of the regulatory complex (Figure 1, Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies might provide additional explanations for the contrasting HSP90 binding behavior of BRAF Δβ3-αC mutants (100,101). Using cryo-electron microscopy (cryo-EM), it was shown that the HSP90/CDC37 complex binds to the C-lobe of the kinase domains of BRAF and RAF1, while the latter, which shows higher affinity to the chaperone complex, also binds to the N-lobe and in the vicinity of the Δβ3-αC segment (101).…”
Section: Discussionmentioning
confidence: 99%
“…If the HSP90 ATPase activity is inhibited pharmacologically, HSP90 cannot load new clients through CDC37 and kinases that are normally HSP90 clients are instead subjected to ubiquitin-mediated degradation 11 . Structures of HSP90 and CDC37 in complex with cyclin-dependent kinase 4 28 , CRAF 29,30 , and BRAF(V600E) 31 revealed that the chaperone complex binds to a partially unfolded conformation of the kinase domain. Like other chaperones, it is likely that this interaction prevents further unfolding and aggregation of the client kinase domains that would be deleterious to the cell.…”
Section: Introductionmentioning
confidence: 99%